Heterogeneous Impact of Victimization on Sense of Safety: The Influence of Past Victimization - Scherg, Rune H. (Victims & offenders, 2022)
It is well-established that recent victimization increases fear of crime, but less is known about the effect of past victimization. Using data from a large panel survey (N = 27,004) combined with register data on past victimization, we examined how past and recent victimization impacts a sense of safety in Denmark. Overall, we found no main effect of past victimization on sense of safety. However, for recurrent victims, past victimization impacts current sense of safety in a heterogeneous way. The results suggest that past adversity can function both as an amplifier and as an attenuator of the effects of victimization on fear of crime.